MODERATED MEDIATION MODEL OF TEAM CONFLICT AND CONFLICT MANAGEMENT APPROACH ON RELATIONSHIP BETWEEN CREATIVE LEADERSHIP AND TEACHER INNOVATION PERFORMANCE IN PUBLIC UNIVERSITIES, GUANGDONG PROVINCE - Jing, Wang; Moonmuang, Sukhum; Pruettikul, sataporn (วารสารนิสิตวัง, 2025)
The objectives of this research were (1) To research on the Impact of Creative Leadership in Public Universities in Guangdong Province on Teachers' Innovation Performance. (2) To research the mediating role of team conflict in creative leadership and teacher innovation performance in public universities in Guangdong Province, and (3) To research the moderating effect of conflict management methods on team conflict and teacher innovation performance. The population of this research were 2749 teachers engaged in design and art education at 21 public higher education institutions in Guangdong Province. The sample was determined using G* Power software and included 547 teachers, selected through a proportional stratified random sampling method. The data were collected using a five-point rating scale questionnaire. The statistical methods used for data analysis included confirmatory factor analysis and structural equation modeling. The research results indicated that: (1) Creative leadership positively affected the innovation performance of teachers in public universities in Guangdong Province; (2) Team conflict in public universities in Guangdong Province had a mediating effect between creative leadership and teacher innovation performance, with stronger creative leadership leading to weaker team conflict; (3) The conflict management approach had a moderating effect on team conflict and teacher innovation performance. When conflict management was at a high level, weaker conflict was associated with higher teacher innovation performance. The above conclusions suggested that creative leadership in universities enhanced teachers' innovation performance and further promoted innovation by reducing team conflicts, while high-level conflict management methods mitigated the adverse effects of conflicts on innovation. Therefore, university administrators should have focused on cultivating creative leadership, managing team conflicts effectively, and improving conflict management skills to foster the innovative development of universities